2016
DOI: 10.1097/dbp.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Youth Screen Time and Behavioral Health Problems

Abstract: OBJECTIVE The purpose of the current study was to examine the indirect effect of youth screen time (e.g., television, computers, smartphones, video games, and tablets) on behavioral health problems (i.e., internalizing, externalizing, and peer problems) through sleep duration and disturbances. METHODS We assessed a community sample of parents with a child in one of three developmental stages: young childhood (3 – 7 yrs.; N = 209), middle childhood (8 – 12 yrs.; N = 202), and adolescence (13 – 17 yrs.; N = 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 45 publications
(48 reference statements)
6
50
0
1
Order By: Relevance
“…The results of this study confirmed the negative impact of video games use on children's sleep quality, specifically concerning sleep onset and daytime sleepiness. Our results are supported by previous studies that demonstrated the negative impact of children's use of electronic devices before bedtime (Beyens & Nathanson, 2018;Brunborg et al, 2011;Cespedes et al, 2014;Gradisar et al, 2013;Higuchi et al, 2005;Hysing et al, 2015;LeBourgeois et al, 2017;Moorman & Harrison, 2018;Nathanson & Beyens, 2016;Oka et al, 2008;Parent et al, 2016;Weaver et al, 2010).…”
Section: Studysupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study confirmed the negative impact of video games use on children's sleep quality, specifically concerning sleep onset and daytime sleepiness. Our results are supported by previous studies that demonstrated the negative impact of children's use of electronic devices before bedtime (Beyens & Nathanson, 2018;Brunborg et al, 2011;Cespedes et al, 2014;Gradisar et al, 2013;Higuchi et al, 2005;Hysing et al, 2015;LeBourgeois et al, 2017;Moorman & Harrison, 2018;Nathanson & Beyens, 2016;Oka et al, 2008;Parent et al, 2016;Weaver et al, 2010).…”
Section: Studysupporting
confidence: 91%
“…Concerning the use of video games and its frequency during childhood (Parent et al, 2016), recent research has examined the influence of general technology use on sleep quality and sleep habits of children and adolescents (Beyens & Nathanson, 2018;Cain & Gradisar, 2010;Calamaro, Mason, & Ratcliff, 2009;Genuneit et al, 2018;Kevitiyagala et al, 2011;Moorman & Harrison, 2018). Hysing and colleagues (2015) developed a correlational study with 9.846 students to assess their sleep quality, considering a daily use of electronic devices before bedtime.…”
Section: Sleep Quality and The Use Of Video Games By School-aged Chilmentioning
confidence: 99%
“…(Lissak, 2018). Excessive screen time can cause sleep disorders in childhood and adolescence and these sleep disorders are linked to internalizing, externalizing, and peer problems (Parent, Sanders, & Forehand, 2016). In our study, we found that screen time predicts conflicts with parents, academic problems, negative influence in friendships (risk for negative friendships and harm), and sleep problems according to parents' reports.…”
Section: Discussionmentioning
confidence: 47%
“…Nevertheless, the purpose of this study was to examine sleep problems in otherwise healthy children and in relation to various socio-demographic factors. An additional limitation is that factors like excessive noise in the environment, sleeping with a pet in the room, or habits, like computer or other devices use, which are known to be associated with shorter sleep duration or higher prevalence of sleep disturbances (11,28,29) were not examined. However, as our results show, among the studied subgroups, no difference was observed in sleep initiation time, a factor which could be attributed to the use of an electronic device prior to sleep; on the contrary, the observed differences were in the time children were awakened.…”
Section: Sleep Duration > 9 Hmentioning
confidence: 99%